Fertilizer effects on some biochemical characteristics of Helianthus tuberosus l (Mongolian Journal of Agricultural Sciences, 2019)
In this research, we purposed to study some biochemical characteristics and effects of fertilizers on the accumulation of inulin polysaccharides in the tubers of Helianthus tuberosus L. For this purpose, three types fertilizers of organic, organic-mineral complex and mineral mixed pellets were used, and the inulin polysaccharide content was determined optical density using spectrophotometer in 285 nm light range. The content of the inulin polysaccharide was the highest in control sample to 31.0% and the lowest in mineral mixed pellets fertilizer to 9.9%. From this point of view, mineral mixtures fertilizer negatively affect the accumulation of inulin is polysaccharide. Protein analysis results shows that two variants with mineral-containing fertilizers give more protein content to control samples, particularly, leaf proteins are 5.08% and 4.21% and the tuber protein is 2.79% and 2.37%. It is proved that mineral fertilizers have a positive effect on protein synthesis.Булцуут цэцгийн (helianthus tuberosus l) биохимийн зарим үзүүлэлтэд бордооны нөлөөХураангуй: Бид энэ удаа Булцуут цэцгийн биохимийн зарим үзүүлэлт болон булцуун дахь инулины полисахаридын хуримтлалд бордооны үзүүлэх нөлөөг судлах зорилго тавилаа. Үүний тулд 3 төрлийн буюу органик, органик-эрдэс нийлмэл, эрдэсхолимог үрлэн бордоонуудаар булцуут цэцгийг бордож ургуулан инулины полисахаридын агууламжийг 285 нм гэрлийн мужид оптик нягтыг нь спектрофотометр ашиглан тодорхойлсон. Инулины полисахаридын агууламж нь хяналтын хувилбар дээр хамгийн өндөр буюу 31.0%, харин эрдэс бордоо хэрэглэсэн хувилбар дээр хамгийн бага буюу 9.9% байв. Эндээс дүгнэхэд эрдэс холимог үрлэн бордоо нь инулины полисахаридын хуримтлалд сөргөөр нөлөөлж байгааг харуулж байна. Харин булцуу болон навчиндуургийн агууламж тодорхойлсон дүнгээс харахад хяналттай харьцуулахад органик-эрдэс нийлмэл бордоогоор бордсон хувилбарт навчны уураг 5.08%, булцууны уураг нь 2.79%, эрдэс холимог үрлэн бордоотойд 4.21%, 2.37%-иар тус тус илүү байна. Энэ нь эрдэс бордоо уургийн нийлэгжилтэнд эерэг нөлөөтэй болохыг харуулж байна.Түлхүүр үг: Инулин, уураг, эслэг, шим тэжээлийн элемент